Notions of Women’s Issues in The Satri Thai Magazine (1925-1927) - Rattanaphan, Chutacaphat; Jatuthasri, Thaneerat; Polmuk, Chairat (Journal of Thai Studies, 2024)
Background and objective (s): Published from 1925-1927, The Satri Thai Magazine became a platform for female writers and readers during the reign of King Rama VII. Remarkably, the magazine was mainly managed by women and declared its strong stance on women’s issues. The magazine regularly published articles and fictional work that discussed women’s issues, such as gender inequality, marriage and fashion. While there exists scholarly writing about the magazine, the topic of women’s issues remains unacknowledged. The author of this article examined The Satri Thai Magazine as a case study to explore notions related to women’s problems. The study also aimed to shed light on the changing status of women in 1920s Siam as the country encountered the concept of modernity. Methodology: The research for this article relied on a literary approach of textual analysis to analyze thematic components, as well as the compositional strategies that authors deployed to convey notions of women’s issues. The study also incorporated a feminist perspective that places an emphasis on femininity and issues of female gender roles to illuminate the notions of women’s issues presented in The Satri Thai Magazine. Main result: The study found that articles published in The Satri Thai Magazine were largely concerned with women’s issues, namely, gender relations, female education and profession, women’s behavior and morality, and women’s appearance. These notions reflect changes in Thai society during its transformation into modernity whereby the idea of sexual equality in legal, educational and professional domains became dominant. At the same time, women’s ethical conduct, manners and physical appearance remained preserved as core values. These notions reflected the status of women in modern Thai society, permeated with contradictions and debate on femininity. These notions also reflect the role of The Satri Thai Magazine as a platform that voiced women’s problems and provided advice on how to live in a modern world. Relevance to Thai Studies: This study explored Thai literary works in the context of Thai society during the reign of King Rama VII in order to understand the construction of Thai femininity in the modern era. Articles analyzed in this study reveal that Thai femininity in this period can be defined by the continuity with traditional notions of womanhood and the adaptation to suit the idea of modernized women. Conclusion: This analysis of notions of women’s issues in The Satri Thai Magazine reflects the cultural history during the reign of King Rama VII during which Thai society was transitioning into the modern world, while by and large remaining a male-dominated society. However, it can also be seen that the magazine provided a platform for women to challenge patriarchal power and establish new status and gender roles for women through a woman-oriented public space. Writers for this magazine employed various strategies to criticize patriarchy and encourage women to adapt to changes.